Watership Down Perspectives On and Beyond Animated Violence - Lester, Catherine (Animation: Key Films/Filmmakers, 2023)
Watership Down (Martin Rosen, 1978) is as controversial as it is beloved. Whether due to the tear-jerking hit song 'Bright Eyes' or its notorious representation of violence inflicted by and upon animated rabbits, the film retains the ability to move and shock audiences of all ages, remaining an important cultural touchstone decades after its original release. This open access collection unites scholars and practitioners from a diversity of perspectives to consider the ongoing legacy of this landmark of British cinema and animation history. The authors provide nuanced discussions of Watership Down's infamous animated depictions of violence, death and its contentious relationship with child audiences, as well as examinations of understudied aspects of the film including its musical score, use of language, its increasingly relevant political and environmental themes and its difficult journey to the screen, complete with behind-the-scenes photographs, documents and production artwork. As the first substantial work on Watership Down, this book is a valuable companion on the film for scholars, students and fans alike. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0licence on bloomsburycollections.com.